THE EFFECT OF BETA GLUCAN OF SACCHAROMYCES CEREVISAE ON THE INCREASE OF THE NUMBER OF BRAIN CELLS IN SUBSTANTIA NIGRA BRAIN OF PARKINSON’S WISTAR STRAIN RAT (RATTUS NORVEGICUS) MODEL INDUCED WITH ROTENONE - Rahayu, Masruroh; Kurniawan, Shahdevi Nandar; Anggraini, Dini Jatiya (Malang Neurology Journal, 2015)
Background. Beta glucan from Saccharomyces cerevisae is very potential to be used as a regenerative therapy of Parkinson's disease. Beta glucan can increase the mobilization of hematopoietic stem cells (HSCs) from the bone marrow into the damaged tissues.Objective. To find out the effects of the addition of Saccharomyces cerevisae toward the number of brain cells in substantia nigra Parkinson’s rat model.Methods. Experimental research in vivo using the draft of randomized post test only controlled group design.Results. Treatment Group 3 (72 mg/kgBB) was a group with the largest number of brain cells than the other treatment groups. Statistical data obtained showed that the average number of brain cells in negative control group was 192.00 cells; positive control amounted to 116.80 cells; Treatment 1 amounted to 135.40 cells; Treatment 2 amounted to 140.80 cells; and Treatment 3 amounted to 161.80 cells.Conclusion. The addition of Saccharomyces cerevisae with a dose of 18mg/kgBB, 36mg/kgBBdan 72mg/kgBB is able to increase the number of brain cells in the substantia nigra of the brain of Parkinson’s Strain Wistar rat model significantly.